2021
DOI: 10.1016/j.psychres.2021.114222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an eight-week, online mindfulness program on anxiety and depression in university students during COVID-19: A randomized controlled trial

Abstract: The COVID-19 pandemic has had adverse mental health effects for many groups in British society, especially young adults and university students. The present study reports secondary outcomes (i.e., symptoms of anxiety and depression) from a randomized waitlist controlled trial, with a one-month post-intervention follow-up, on the effects of a guided, eight-week mindfulness program delivered online during the COVID-19 pandemic among students at the University of Oxford. Longitudinal multilevel models showed grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 23 publications
4
73
2
3
Order By: Relevance
“…All incorporated studies assessed the effectiveness of internet-based psychological intervention programs for reducing stress, anxiety, and depression among university students during COVID-19 social distancing. Seven studies were conducted by researchers in American universities [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ], two studies in Asian universities [ 39 , 40 ], and one study in an African university [ 41 ]. Meta-analyses were performed separately on interventions for reducing stress, anxiety, and depression ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All incorporated studies assessed the effectiveness of internet-based psychological intervention programs for reducing stress, anxiety, and depression among university students during COVID-19 social distancing. Seven studies were conducted by researchers in American universities [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ], two studies in Asian universities [ 39 , 40 ], and one study in an African university [ 41 ]. Meta-analyses were performed separately on interventions for reducing stress, anxiety, and depression ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 5086 students 18 years or older participated in the studies. Three of the studies reported an age range of participants [ 37 , 39 , 41 ], while the others just reported that students were 18 years or older. Most of the included studies were conducted with undergraduate students, while one study [ 39 ] featured graduate students.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Examination of the forest plot showed no potential study outliers. After removing one study by Simonsson et al [ 37 ] in sensitivity analysis, the pooled effect was reduced to insignificance.…”
Section: Resultsmentioning
confidence: 99%